Anthropometric characteristics and somatotype in elite Chilean rowers - Gutiérrez-Leyton, L.; Zavala-Crichton, J.; Fuentes-Toledo, C.; Yánez-Sepúlveda, R. (International Journal of Morphology, 2020)
The aim of the study was to describe the anthropometric characteristics and somatotype of the Chilean selected rowers. Twenty one 21 athletes (6 women and 15 men) with an average age of 18.66 ± 2.58 years for women and 22.06 ± 4.71 years for men were evaluated. The study was conducted prior to the Pan American qualification in Lima 2019. At the time of the evaluations, the athletes were concentrated in the Olympic Training Center (CEO) located in Curauma in the Valparai´so region of Chi- le. The anthropometric evaluations were carried out based on the restricted profile of 25 variables proposed by Kerr and Ross that allowed the fractionation of the body mass into 5 components (tissue: skin, residual, bone, adipose and muscle). The wingspan, the iliospinal height and the folds of the biceps and supracrestide were also measured; all measurements were based on the protocol of marking and evaluation proposed by ISAK. Carter and Heath method was used to calculate the somatotype, describing the components of endomorphy, mesomorphy and ectomorphy respectively. The results showed a percentage of fat in men of 19.34 ± 1.59 % and in women of 27.08 ± 3.6 % (p = 0.003), the muscle mass of men was 52.69 ± 1.78 % and in women of 45.68 ± 4.19 % (p = 0.003), a balanced mesomorphic somatotype was observed in both men (1.7-5.3-2.2) and women (2.5-3, 7-2.7). It is concluded that the Chilean rowing selected have a high development of muscle mass and a low percentage of fat mass, in addition to a balanced mesomorphic somatotype.